Pengaruh Manajemen Modal Kerja Terhadap Profitabilitas Perusahaan pada Perusahaan Rokok yang Terdaftar di Bursa Efek Indonesia - Kautsari, R.rr Ken Berlian (Jurnal Ilmiah Mahasiswa FEB, 2013)
The study aims at examining the effect on working capital management as well on profitability of the tobacco companies listed on Indonesia Stock Exchange. This research describes the influence of four independent variables namely Inventory turnover period, Receivables Conversion Period, Payables Defferal Period, and Cash conversion cycle on the return on asset of firms. Debt ratio and firm size have been used as control variables. This research included in the type of quantitave and population research. This research used 3 firms namely PT Gudang Garam Tbk., PT Hanjaya Mandala Sampoerna Tbk., and PT Bentoel Internasional Investama as a population for a period of 7 years from 2005- 2011. To analyze the data, multiple linear regression is used. The result show that there are a strong negative relationship between Inventory turnover period, Receivables Conversion Period, and Cash conversion cycle and return on asset of the firms. Payables Defferal Period does not affect on the return on asset of the firms. It means that as the cash conversion cycle increases it will lead to decreasing return on asset of the firm. Therefore, managers can create positive value for the shareholders by reducing the cash conversion cycle to a possible minimum level. Keywords : Working Capital Management, Profitability, Cash Conversion Cycle